Pengaruh Konten Media Sosial Instagram pada Akun @selatan.florist terhadap Minat Beli Followers: Pendekatan Elaboration Likelihood Model - Retno Wulandari; Budi Santoso (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The rapid advancement of technology has pushed business actors to rely on social media as their primary promotional channel. On the @selatan.florist account, several obstacles were identified in content production — particularly in feeds, stories, and reels — concerning visual appeal, upload consistency, and the depth of informative value delivered to the audience. This study examines the extent to which social media content produced by @selatan.florist affects followers' purchase intention. The Elaboration Likelihood Model (ELM) serves as the theoretical lens, explaining how individuals process persuasive messages and form attitudes in response. A quantitative methodology was applied, with a structured questionnaire distributed to 152 respondents who follow the @selatan.florist account. Simple linear regression analysis reveals a statistically significant influence of social media content on purchase intention. The R² value of 66.3% indicates that visual aesthetics and informational depth in the account's content are decisive factors in converting audience attention into purchasing behavior.